Անտոն Մատաթիա Գարագաշեանի փիլիսոփայութեան դասագիրքերը եւ գիտապաշտութիւնը - Էրզուրումլուօղլու, Ճան (տպ. Atlas)
During the second half of the 19th century, in line with Europe, some Western Armenian intellectuals started to become acquainted with positivist and materialistic ideas. One of these intellectuals was Anton Madatya Karakashian, who, under the influence of the German materialist philosopher Buchner, quit his clerical status and adopted a scientific worldview. Karakashian propagated scientific views in some of his articles, but his main contribution was his Armenian textbooks on philosophy and logic. These books reflect his scientific worldview which stands closer to the empiricists. Furthermore, these books played an important role in introducing Western philosophy to Armenian students. Karakashian was also a well-known Armenologist, educator, linguist and a popular textbook author. He promoted critical thinking, yet he was conservative in terms of language and campaigned for the revival of Krapar (classical Armenian), and even launched a journal in classical Armenian.
Keywords: Փիլիսոփայութիւն